Evaluation of the Use of Structural Gamification-Based Applications by Users in Makassar City, Indonesia - Andi Fitria Idham; Ade Putrawan; Firdi Athaya; Fitrah Ramadhan; Arnis Puspitha Rasyid (Jurnal Keperawatan Indonesia, 2025)
Structural gamification is a trending concept in today’s application landscape that leverages various elements and features from game design for nongame contexts. This concept has become increasingly common in various health applications today, such as Lose It!, Fat Secret, and Google Fit. This study aims to evaluate respondents’ use of structural gamification-based health applications. The research method employed in this study is quantitative and descriptive, involving data collection through questionnaires administered from July 2023 to September 2023 in Makassar City, Indonesia. The research results indicate that 90% of the respondents appreciated the ease of access and attractive interface of structural gamification-based health applications, while 35% disliked these apps’ high battery consumption. The majority rated them as 8 and as 8 or 9 on a scale of 1 to 10 in terms of usefulness and effectiveness, respectively. The findings of this study are expected to provide recommendations for nursing interventions that use technology to promote healthy lifestyle modifications in public health management. Keywords: gamification, goal-oriented, self-regulation   Abstrak Evaluasi Pemanfaatan Aplikasi berbasis Structural Gamification pada Pengguna di Kota Makassar, Indonesia. Structural gamification merupakan konsep aplikasi yang sedang tren saat ini, konsep ini memanfaatkan berbagai elemen dan fitur yang terdapat pada desain game untuk konteks aplikasi non-game. Konsep berbasis structural gamification semakin umum ditemukan dalam berbagai aplikasi kesehatan saat ini, seperti yang ada pada aplikasi Lose It!, Fat Secret, Google Fit. Riset ini bertujuan untuk mengevaluasi pemanfaatan aplikasi kesehatan berbasis structural gamification terhadap pengguna. Metode yang digunakan dalam riset ini adalah kuantitatif deskriptif, dengan pengumpulan data melalui kuesioner yang dilakukan pada bulan Juli-September 2023 di Kota Makassar. Hasil penelitian menunjukkan bahwa 90% responden menyukai aspek kemudahan akses dan tampilan yang menarik, sedangkan 35% responden tidak menyukai kebutuhan baterai yang tinggi pada pengguna. Pada skala manfaat mayoritas menjawab pada skala 8 dari 10, dan pada skala efektivitas mayoritas menjawab pada skala 8 dan 9 dari 10. Temuan penelitian ini diharapkan dapat memberikan rekomendasi intervensi keperawatan yang memanfaatkan teknologi untuk modifikasi gaya hidup sehat dalam manajemen kesehatan masyarakat. Kata Kunci: gamifikasi, orientasi tujuan, regulasi-diri